PENGARUH BIAYA KUALITAS TERHADAP PRODUK RUSAK PADA CV. AKE ABADI - Alfarezi, Vrigel Vasya (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2023)
Quality product can be achieved in companies with always conduct surveillance and improvement of the quality of its products. Costs incurred in connection with efforts to improve the quality of the product is called the cost of quality. The purpose of this study was to determine the influence of the quality costs consist of the costs of prevention and appraisal costs against defective product. The research was conducted on the CV. Ake Abadi, which is a company engaged in the manufacturing field. Data type that used namely quantitative and qualitative data. The results showed that the factors causing faulty products caused by pests and employee errors in the transport of goods from factory to cost does not affect the quality of the product is defective it can be seen from the results of the t test variable costs of production significance. This means that the cost of quality, does not significantly affect the defective product, the correlation coefficient is low, which means there is a weak relationship between the independent veriabel whereas test results determination coefficient (Kd) showed equal straight.